Strategic Business Analysis on Investment Method of Coal Transshipment(Case Study of PT. KPC) - Mantiri, Simon Aloysius; Siahaan, Uke MMP. (The Indonesian Journal of Business Administration, 2013)
The economic slowdown in 2012 has exerted a significant impact on the coal industry. The fluctuation of demand for thermal coal, particularly from a large and growing market, forces producers to revise production plans set long before. Imposing a cost-saving mode throughout its operations, KPC can still maintain its sales volume for customers, while pursuing its strategy to increase coal production. According to Gede Ngurah Ambara, Manager of Business Performance Improvement at KPC, presenting at the 11th Annual Coal Market Conference 2013, KPC plans to produce a total of 66,66 Mt coal this year, still on track towards a 70 Mt production target in 2014. However, the capacity limitation of its coal loading facilities has impelled KPC to upgrade existing infrastructure. With total throughput of 42.5 Mt in 2012, there is a gap of around 27.5 Mt to be considered in 2014. While the main loading facility, Tanjung Bara Coal Terminal (TBCT), is being upgraded, transshipment could be the optimal alternative solution to ensure continuity of the coal supply chain.Playing an important role as an alternative to and complement of the TBCT operation, there must be intelligent selection of transshipment facilities. Thus, this project aims to decide on a suitable transshipment option to fill the gap in coal production. Options include an additional Floating Crane (FC), Floating Transfer Station (FTS) or Floating Coal Storage (FCS). The main factor governing the selection is maintaining a reliable coal supply to oceangoing vessels, avoiding bottlenecks, along with continued efforts to reduce demurrage.In the comparison of the methods, both a quantitative and qualitative assessment will be applied. The quantitative assessment used is an investment analysis of NPV, IRR, with WACC derived from Bumi Resourcesâ€™ financial statement of 2012, while for the qualitative one, a concept from LD Ports & Logistics, elaborating a Transshipment Solution Decision Model,will cover operational, environmental and other important factors impacting coal loading operations, as applied to KPC. With the assumption of 15 Mt of additional production to be handled by transshipment operations (while the remaining gap will be handled by developed TBCT), it is clear that in the KPC context, Floating Coal Storage is the optimal choice, compared to other options, as buffer storage of around 60,000 t will ensure the reliability of transshipment to oceangoing vessels, and will shorten turnaround and laycan time, thus minimizing any demurrage penalties. Comparing the calculation of lease vs. purchase options for Floating Coal Storage (FCS), along with the consideration of points from the KPC Transshipment Solution Decision Model, it is clear that leasing the facility is a wiser option for the remainder of the CCoW (Coal Contract of Work) period,terminating in 2021.As an additional aspect of this research, Porterâ€™s 5 Forces and a SWOT analysis of the company are to be conducted, with the intention of providing a broader perspective onboth the coal industry and company performance, which will assist in determining whether this project is feasible for implementation. Â Keywords : transshipment, reliability, bottleneck, demurrage, throughput